Pengaruh Indeks Pembangunan Manusia dan Pengeluaran Rutin Terhadap Pertumbuhan Ekonomi di Provinsi Papua - Ali Syahbana; Anita Rusianti; Susiani Susiani (Economics and Digital Business Review, 2023)
The objectives to be achieved in this study are (1) To determine the effect of the education index on economic growth in Provinsi Papua (2) To determine the effect of the health index on economic growth (3) To determine the effect of the per capita expenditure index on economic growth (4) To determine the effect routine government spending on economic growth. The approach in this research is quantitative research, a method used to examine natural object conditions where the researcher is the key. The research method used multiple linear regression analysis, correlation coefficient analysis, analysis of the coefficient of determination, and hypothesis testing. Based on the results of the study, it was found that partially (1) the education index has a positive but not significant effect on economic growth in Provinsi Papua City (2) the health index has a positive but not significant effect on economic growth (3) the per capita expenditure index has a positive but not significant effect on economic growth (4) routine expenditure has a positive but not significant effect on economic growth